Effectiveness of an educational Program on improving nurses’ knowledge regarding Apgar score in Akre city - Shevan Younis Othman; Mohammed Haydar Mosa (Kufa Journal for Nursing Sciences)
Background: Newborns are tested shortly after birth to get their Apgar score. This assessment evaluates an infant’s cardiac function, muscle tone, and other essential characteristics to establish whether additional investigations or actions that can be considered as emergency procedures are needed.